Labor Trafficking in North Carolina: A Statewide Survey Using Multistage Sampling, 2014-2016 - Zhang, Sheldon ([Verlag nicht ermittelbar], 2018)
These data are part of NACJD's Fast Track Release and are distributed as they were received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed except for the removal of direct identifiers. Users should refer to the accompanying readme file for a brief description of the files available with this collection and consult the investigator(s) if further information is needed. The study contains data from face-to-face interviews of 404 migrant farmworkers in North Carolina. The data was collected to produce reliable estimates of the prevalence of labor trafficking victimization among farmworkers in North Carolina. Additional objectives included improving the ability to identify potential trafficking cases as well as investigating the types of victimization migrant workers experienced. This study includes one SPSS data file: LaborTraffickingNC_PUF.sav (140 variables, 404 cases). The study also includes three syntax files: Tables-1-6-code.sps Table-7-code.docx variable-creation.sps